The effects of mud contamination to wellbore stability - Surej, K. S.; Samsuri, Ariffin; Z., Zularisam (1997)
The paper describes a series of laboratory works for wellbore instability due to mud contamination by different mud system. Three favorite mud systems, Water Based mud, Oil Based Mud and Inverted Emulsion Mud has been used for the research. The perforated wellbore model invaded with these mud systems and the stability test conducted to suggest the best mud system which gives best stability. The perforation pattern also studied in the research. In general, it is found that the Oil Based Mud system gives the best stability followed by Inverted Emulsion Mud and Water Base Mud system regardless of the perforation pattern. The perforation pattern analysis shows that the spiral pattern exhibits the most stable pattern followed by inplane and inline.